(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
The main objective of this qualitative research is to understand the didactics for creation in the performing arts, implemented by a group of teacher-artists, in the framework of joint experiences of creation research through the methodological design presented by Jara 2011 systematization of experience that has 5 phases: the starting point, the initial questions, the initial questions, the background reflection and the points of arrival. The instruments and procedures for the collection and analysis of information in this case are the interview (semi-structured), the learning recovery form and the ordering and reconstruction matrix.